Leader motivation identification: relationships with goal-directed values, self-esteem, self-concept clarity, and self-regulation - Van Doorn, Judy R.; Raz, Cody J. (Frontiers in Organizational Psychology, 2023)
Motivation tied to workplace performance is key to organizational effectiveness with visionary leadership. Identifying leaders on a spectrum of different motivation styles, culture values, self-concept clarity, self-esteem, and self-regulation factors may assist with company training goals and impact global, organizational performance. The purpose of this study is to assess leader motivation through traits, cultural values, and behavior approaches including 1) motivation to lead style differences subsuming affective-identity, social-normative, and non-calculative styles; 2) motivation to lead style relationships to culture values, global self-esteem, and self-concept clarity; and, 3) motivation to lead styles to individual self-regulation subsuming goal-setting and impulse control behaviors. Participants (N = 1121) self-reported work and military experiences with managerial or supervisory experience. Research evidence included culture values of power and self-direction predicted affective-identity style and power, achievement, and security values positively predicted social-normative style. Leader self-regulation factors of goal-setting and impulse control were positively predicted by achievement, self-direction, conformity and benevolence values. Tradition and security values negatively predicted goal-setting and values of tradition, security, stimulation, and universalism negatively predicted impulse control. Meaningful differences were found between motivation to lead styles with values, global self-esteem, and self-regulation factors. This study may assist with identifying potential organizational leaders through motivation to lead assessment and leader training needs focused on goal-setting and self-regulation diplomacy.